2015
DOI: 10.1007/s00464-015-4677-9
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Nissen fundoplication after endoscopic radiofrequency ablation of Barrett’s esophagus

Abstract: HALO RFA is a safe procedure, with high rate of success in complete eradication of BE in symptomatic GERD patients. LNF provides good protection for neosquamous epithelium and in selected group of patients could be offered as a first line of treatment after HALO RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…One of the studies revealed that patients with IM and dysplastic BE who were submitted to ARS after RFA have statistically lower incidence of persistent and recurrent BE opposed to those receiving PPI's on a 1‐year follow‐up . In another study, which prospectively evaluated BE recurrence after RFA, ARS proved to be superior over the PPI regimen in patients with long BE (≥4 cm), with significantly lower incidence on a 3‐year follow‐up . Recent data that covered a 5‐year follow‐up of patients included in randomized Ablation of Intestinal Metaplasia Containing Dysplasia trial (AIM Dysplasia Trial) pointed out that recurrence of BE is most frequent in the first year following RFA .…”
Section: Shall We Ablate Patients Before or After Antireflux Surgery?mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the studies revealed that patients with IM and dysplastic BE who were submitted to ARS after RFA have statistically lower incidence of persistent and recurrent BE opposed to those receiving PPI's on a 1‐year follow‐up . In another study, which prospectively evaluated BE recurrence after RFA, ARS proved to be superior over the PPI regimen in patients with long BE (≥4 cm), with significantly lower incidence on a 3‐year follow‐up . Recent data that covered a 5‐year follow‐up of patients included in randomized Ablation of Intestinal Metaplasia Containing Dysplasia trial (AIM Dysplasia Trial) pointed out that recurrence of BE is most frequent in the first year following RFA .…”
Section: Shall We Ablate Patients Before or After Antireflux Surgery?mentioning
confidence: 99%
“…In this manner, after the hiatal hernia is reduced, esophagus encircled and pulled into the abdomen, esophageal lumen is narrowed, so that RFA electrodes apply more closely to the mucosa. Concomitant ARS and RFA was proven to be safe, not time‐consuming, and it was performed in conjunction with the basic rules of RFA procedure, avoiding potential pitfall of choosing wrong balloon diameter . To conclude, ARS as the addition to RFA of BE may play an important role in recurrence prevention, which, however, has to be demonstrated in sufficiently powered studies.…”
Section: Shall We Ablate Patients Before or After Antireflux Surgery?mentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that post-ablation the neosquamous epithelium is potentially more prone to reflux injury [145], possibly increasing the risk of BE recurrence. A recent study found decreased BE recurrence after RFA with Nissen fundoplication versus PPI therapy, in the subgroup of patients with long-segment BE and a hiatal hernia >3 cm [146]. However, current data as to any incremental benefit of a surgical anti-reflux procedure compared with medical therapy after successful RFA remains inconclusive [147, 148], and in general the indications for consideration of fundoplication after RFA remain similar to those in the general GERD population.…”
Section: Managementmentioning
confidence: 99%
“…There are literature reports justifying laparoscopic antireflux surgery after radiofrequency ablation of Barrett's esophagus (BE), as it has been proven that the addition of fundoplication may result in less persistent or recurrent BE, especially in patients with longer BE segments and a hiatal hernia of > 3 cm [12,13]. Future studies in this direction are certainly warranted.…”
Section: Early Esophageal Lesionsmentioning
confidence: 99%